Improved Biological Activity and Stability of enzyme L-Asparaginase in Solid Lipid Nanoparticles Formulation: Controlled release formulation of L-Asparaginase - Sharma, Gazal; Rath, Goutam; Goyal, Amit (Journal of Drug Delivery and Therapeutics, 2019)
To protect the biological activity of an enzyme during the development of formulations is one of the biggest challenges. The tetrameric form of L-Asparaginase is used to treat Acute Lymphocytic Leukaemia. It possesses shorter in vivo half–life. Using a modified (water/oil)/water-emulsion method followed by solvent evaporation L-Asn was successfully encapsulated at the core of Solid Lipid Nanoparticles made of lipid glyceryl monostearate. This study elucidated that the preparation of L-Asn loaded SLN develop a colloidal formulation with enhanced activity. The in-vitro release proﬁle of the enzyme revealed ﬁrst bursts has been increased. The study of the lyophilised formulation also shows that the enzyme holds its biological activity and retains its particle size distribution. Consequently, by using an apt combination of homogenisation speed, temperature and additives the storage and biological activity of L-Asn in SLN formulation can be improved. Keywords: L-Asparaginase, Solid Lipid Nanoparticles, Controlled release, Lymphocytic Leukaemia